2023
DOI: 10.1186/s40824-023-00343-4
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the tumor microenvironment with biotechnology

Abstract: The tumor microenvironment (TME) is a unique environment that is developed by the tumor and controlled by tumor-induced interactions with host cells during tumor progression. The TME includes immune cells, which can be classified into two types: tumor- antagonizing and tumor-promoting immune cells. Increasing the tumor treatment responses is associated with the tumor immune microenvironment. Targeting the TME has become a popular topic in research, which includes polarizing macrophage phenotype 2 into macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…As the basis for tumor survival, the TME provides a material foundation for tumor proliferation, metastasis, and invasion. , The TME is a network surrounding tumor cells and consists of various types of cells. Blood vessels provide oxygen and nutrients and are responsible for removing waste products.…”
Section: Application Of Tumor Microenvironment Modulated Nanoplatform...mentioning
confidence: 99%
“…As the basis for tumor survival, the TME provides a material foundation for tumor proliferation, metastasis, and invasion. , The TME is a network surrounding tumor cells and consists of various types of cells. Blood vessels provide oxygen and nutrients and are responsible for removing waste products.…”
Section: Application Of Tumor Microenvironment Modulated Nanoplatform...mentioning
confidence: 99%
“…Immune system can exert its function of immune surveillance and immune response against tumor cells, which play crucial roles in proliferation, metastasis and treatment resistance of cancers 77 , 78 . Tumor immune microenvironment (TIME) consists of tumor, stromal and immune cells including adaptive and innate immune cells 79 . Current studies have showed remarkable enrichment of m7G regulators in biological processes in TIME, especially immune infiltration 6 .…”
Section: The Roles Of M7g Modification In Immune Cell Biologymentioning
confidence: 99%
“…[16]. Table 1 is the summary of the infections documented in this literature that are resistant to antibiotics [17], [18].…”
Section: How Vaccines Can Help Prevent Antimicrobial Resistancementioning
confidence: 99%